HUBUNGAN POLA KOMUNIKASI ORANG TUA DENGAN PERKEMBANGAN BAHASA ANAK PRASEKOLAH (USIA 2-5 TAHUN) - Nur Hidayati, Rina; Maslahah, Umu (JURNAL KEPERAWATAN BINA SEHAT, 2013)
Preschool period is a period that occurred from late infancy to 2 years up to about the age of 5years. At this age range a rapid growth in the frontal lobe that is characterized by thedevelopment of childrens language skills, therefore, attempts to optimize growth anddevelopment in children is very important one of them by talking or communicating with thechild, the child who got rich verbal environment of the elderly will be a positive benefit. Thepurpose of this study is to identify the relationship Parents Communication Pattern withLanguage Development Preschool (Age 2-5 Years) in PAUD Hidayatul Ilmi Tambak AgugPuri District Mojokerto Regency. Population more than 36 people with sampling a totalsampling techniques. Independent variable in the study is the communication patterns ofparents and the dependent variable is the language development of preschool. Design researchanalytic Cross sectional approach. The data were taken using a questionnaire. The resultsshowed a relationship between parents communication patterns with language development ofpreschool children seen crosstab results obtained by 12 respondents (80%) using a pluralisticcommunication and 8 respondents (88,9%) using konsensual with the childs languagedevelopment in accordance with 24 respondents (66.7%). This suggests that the good ofcommunication pattern can stimulate childrens language development. Families are expectedto improve the delivery of stimulation in the form of good communication to the child, in theform of two-way communication between parents and children and more disscuse withchildren.Keywords: Parents communication pattern, Language development, Preschool